Combined effect of pill refilling and self-medication reminder system on patients’ adherence to tuberculosis treatment during continuation phase in Northwest Ethiopia: a study protocol for randomised controlled trial - Gashu, Kassahun Dessie (BMJ Health Care Inform, 2019)
INTRODUCTION: Patients’ failure to adhere on tuberculosis (TB) treatment leads to drug resistance, relapse and death. Non-adherence to TB treatment is higher during continuation treatment phase. The study aimed to evaluate effectiveness of combined pill refilling and medication reminders on adherence to TB treatment. METHODS AND ANALYSIS: A two-arm randomised controlled trial on adult patients with TB was used during continuation treatment phase. In the first arm, in addition to usual care, participants will receive cellphone-based daily medication and weekly pill refilling reminders. In the control arm, participants will receive only usual care. The study will use a covariate adaptive randomisation technique to balance covariates during allocation. The primary outcome is patients’ adherence to TB treatment and secondary outcomes are attendance to clinic and treatment outcomes. We apply intention to treat with generalised linear mixed model. ETHICS AND DISSEMINATION: Ethical approval was obtained from Institutional Review Board of University of Gondar. Written informed consent was applied during enrolment. We will publish findings in peer-reviewed, scientific journals and conferences. TRIAL REGISTRATION NUMBER: PACTR201901552202539.